Modelling of the vapour–liquid equilibrium of water and the in situ concentration of H3PO4 in a high temperature proton exchange membrane fuel cell - Kazdal, Timur J.; Lang, Sebastian; Kühl, Frank; Hampe, Manfred J. (Journal of power sources, 2014)
The fuel cell technology is a key element for the hydrogen energy economy and therefore crucial for sustainable development. High temperature proton exchange membrane (HT-PEM) fuel cells (FC) can be operated with reformate gas and thus represent an important bridging technology for the energy transition to a renewable energy based system. HT-PEM FCs based on phosphoric acid (PA) are still subject to intense research, investigating the electrolyte behaviour. By enhancing state of the art 2D FEM simulations of FCs with the vapour liquid equilibrium of water-phosphoric acid and evaporation kinetics, a model was created in which the local concentration of PA can be calculated. Knowledge of the concentration field yields the basis for calculating the locally varying ionic conductivity and other physical properties. By describing the volume expansion behaviour of PA it was possible to predict the catalyst particle deactivation due to the swelling of PA. The in situ concentration predicted by the simulation ranges from 96 to 111 wt%. The model was validated using measured data of a single cell design for different temperatures and pressures. By varying the PA content flooding of the simulated fuel cell could be observed and was linked to humidification effects.